2016
DOI: 10.1038/srep37216
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Community-acquired Pneumonia in Children Caused by Re-emergent Human Adenovirus 7d Associated with Higher Severity of Illness and Fatality Rate

Abstract: Human adenoviruses (HAdVs) are highly contagious pathogens causing acute respiratory disease (ARD), such as community-acquired pneumonia. HAdV-7d, a re-emergent genomic variant, has been recently reported in Asia and the United States after a several-decade absence. However, whether HAdV-7d is associated with higher severity than other types is currently unclear. In this study, the clinical and epidemiological investigation showed that fever, cough, and sore throat were the three most common respiratory sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 62 publications
8
68
0
Order By: Relevance
“…Their findings were consistent to ours. Wang et al (15) reported that HRV was associated with severe adult CAP in Chinese; Yu et al (16) reported that human adenovirus 7 type caused higher fatality rate (28.6%) of Chinese child acute respiratory infectious disease than other types. However, their conclusions were almost drew from univariate analyses, and some confounding factors, such as underlying disease, should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings were consistent to ours. Wang et al (15) reported that HRV was associated with severe adult CAP in Chinese; Yu et al (16) reported that human adenovirus 7 type caused higher fatality rate (28.6%) of Chinese child acute respiratory infectious disease than other types. However, their conclusions were almost drew from univariate analyses, and some confounding factors, such as underlying disease, should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of L1 52/55K protein in promoting the formation of infectious virions, the up-regulation of L1 52/55K might explain the rapid growth of the Wuhan strain and this outbreak. In addition, a previous report suggested that the L1 52/ 55K gene, which recombined from HAdV-B16, was a reason for the virulence of HAdV-7 strains predominated in China [32]. The WH strain identified in this outbreak shared 100% identity with this reported L1 52/55K gene.…”
Section: Discussionmentioning
confidence: 55%
“…2,23 However, among the 112 cases in our study, only 4 were diagnosed with viral pneumonia, probably because of a general assumption of bacterial pneumonia. Many previous studies have seriously underestimated the incidence of pneumonia caused by viral infections, especially by new respiratory viruses, which can cause severe pneumonia with a high fatality rate [24][25][26] . Taking the 2003 SARS outbreak as an example, the Asian Development Bank estimated that this epidemic cost Hong Kong ~$6 billion.…”
Section: Discussionmentioning
confidence: 99%